Collaboration in Handling COVID-19 Turbulence from a Threefold Perspective: A Literature Review - Andy Pasaribu; Teguh Kurniawan (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2022)
The crisis due to COVID-19 can be called turbulence and its handling requires cross-border collaboration because complex problems tend to be overcome through multi-actor collaboration in networks and relationships to obtain common solutions. Collaborative governance is present as an instrument for implementing policies for handling COVID-19 to address the government's limitations in material, technical, and resource matters. Using a qualitative approach, this study aims to identify the implementation of collaborative governance in handling COVID-19 by countries in the world in a threefold perspective. This perspective is a new approach in collaborative governance that has the same basis as the Collaborative Governance Regime theory, but tends to narrow the thinking to three layers that support each other in the form of folds: values ??(individuals and policies), decision structures (action situations and sub-systems). policy), and context (external variables, stable parameters, and external events). Public values ??grow from the social context and are articulated in collaborative governance platforms and are important for the government to work on to improve community compliance with government programs. The turbulent COVID-19 situation creates space and decision-making. Each country has different choices, backgrounds, and policies but still bases the process of making and implementing policies on collaborative governance according to their respective preferences. In the folds of policy style and administrative culture, each country has its own dynamics. Countries with sufficient experience in handling outbreaks are able to make administrative adjustments more quickly, which helps speed up the response to the pandemic